2021
DOI: 10.3390/s21092926
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Mounted Bare and Packaged Fiber Bragg Grating Sensors for Measuring Rock Strain in Uniaxial Testing

Abstract: The paper explores the possibility of using high-resolution fiber Bragg grating (FBG) sensing technology for on-specimen strain measurement in the laboratory. The approach provides a means to assess the surface deformation of the specimen, both the axial and radial, through a chain of FBG sensor (C-FBG), in a basic setup of a uniaxial compression test. The method is cost-effective, straightforward and can be commercialized. Two C-FBG; one was applied directly to the sample (FBGBare), and the other was packaged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The refractive index of the core is higher than that of the shell. SMF allows to transmit a single beam of light over a long distance, which makes it suitable for various applications [6]. FBG technology is widely used in engineering and scientific research.…”
Section: Analysis Of Literature Data and Problem Statementmentioning
confidence: 99%
“…The refractive index of the core is higher than that of the shell. SMF allows to transmit a single beam of light over a long distance, which makes it suitable for various applications [6]. FBG technology is widely used in engineering and scientific research.…”
Section: Analysis Of Literature Data and Problem Statementmentioning
confidence: 99%
“…Liu et al [21] wrapped distributed optical fiber around the surface of a rock sample and categorized the damage process into four stages accord-ing to the strain test results. A test on rock uniaxial compression by Isah and Mohamad [22] using bare fiber and encapsulated fiber, respectively, showed that bare fiber was more sensitive than encapsulated fiber. However, encapsulated fiber was found to be more conducive to the test of coordinated deformation of materials.…”
Section: Introductionmentioning
confidence: 99%
“…The continuous development of fiber optic techniques enabled the creation of sensors such as: Bragg gratings, Fabry-Perot (F-P) sensors [1] and based on Brillouin or Raman scattering effects [2]. Those have a broad range of applications: Engineering [3], aviation industry [4], science, and healthcare [5].…”
Section: Introductionmentioning
confidence: 99%